2013
DOI: 10.1136/bmjopen-2012-002159
|View full text |Cite
|
Sign up to set email alerts
|

Mortality (1950–1999) and cancer incidence (1969–1999) of workers in the Port Hope cohort study exposed to a unique combination of radium, uranium and γ-ray doses

Abstract: ObjectivesUranium processing workers are exposed to uranium and radium compounds from the ore dust and to γ-ray radiation, but less to radon decay products (RDP), typical of the uranium miners. We examined the risks of these exposures in a cohort of workers from Port Hope radium and uranium refinery and processing plant.DesignA retrospective cohort study with carefully documented exposures, which allowed separation of those with primary exposures to radium and uranium.SettingsPort Hope, Ontario, Canada, uraniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 26 publications
3
58
0
Order By: Relevance
“…Port Hope, canada (Zablotska et al 2013), or in uranium processing nuclear industries such as Fernald, Ohio, USA (ritz 1999;Silver et al 2013), Mallinckrodt, Missouri, USA (Dupree-Ellis et al 2000) and ArEVA nc Pierrelatte, France (guseva canu et al 2010, 2011; guseva canu and garsi 2012). Millers and nuclear workers are exposed to a variety of occupational risk factors, namely uranium ore dust exposure, external gamma radiation and often radon and silica dust exposure.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Port Hope, canada (Zablotska et al 2013), or in uranium processing nuclear industries such as Fernald, Ohio, USA (ritz 1999;Silver et al 2013), Mallinckrodt, Missouri, USA (Dupree-Ellis et al 2000) and ArEVA nc Pierrelatte, France (guseva canu et al 2010, 2011; guseva canu and garsi 2012). Millers and nuclear workers are exposed to a variety of occupational risk factors, namely uranium ore dust exposure, external gamma radiation and often radon and silica dust exposure.…”
mentioning
confidence: 96%
“…Mortality from cancers of other sites, non-malignant respiratory diseases or renal diseases was increased in single studies, but the number of cases had been small. Presently, only a few studies (Zablotska et al 2013;ritz 1999;Silver et al 2013) provide quantitative exposure-response relationships between the above-mentioned outcomes and internal and external ionizing radiation exposure. A statistically significant positive dose-response relation was recently observed for intestinal cancer and internal organ dose (Silver et al 2013) and a small nonsignificant increase for lung cancer in relation to radon progeny exposure (Zablotska et al 2013).…”
mentioning
confidence: 98%
“…The 90% CI of SMR was applied in 2 studies (34,35); this value was difficult to convert to 95% CI for the present meta-analysis, and the calculation of skewed distribution may have reduced the precision. Another source of bias was the combined colorectal SMR in three individual parts of the colon, small intestines and rectum in several studies (17,26,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), which could increase heterogeneity. Unfortunately, while the type of work-related exposure may be similar, a large-scale study also has significant differences in sensitivity and may have skewed the results of the meta-analysis.…”
Section: Follow-up --------------------------------------------------mentioning
confidence: 99%
“…In spite of these limitations, some studies have reported biologically plausible positive associations between uranium exposure and lung cancer (Ritz 1999, Guseva Canu et al 2011), lymphatic and hematopoietic tumours (Yiin et al 2009, Guseva Canu et al 2011. In addition, excesses have been observed for circulatory diseases and intestinal cancer in single studies (Guseva Canu et al 2012, Silver et al 2013, however up to date few studies examined these outcomes and provided inconsistent results (Zablotska et al 2013, Kreuzer et al 2015b. In order to provide improved estimates of uranium exposure risks, largescale epidemiological studies which address the limitations of previous studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies focusing on the health effects of uranium exposure at later stages of the nuclear fuel cycle have also been performed (e.g. : Dupree et al 1995, Chan et al 2010, Guseva Canu et al 2011, Silver et al 2013, Zablotska et al 2013, Gillies and Haylock 2014, Kreuzer et al 2015b, Zhivin et al 2015, Samson et al 2016 but were generally limited by low statistical power for characterizing exposure-risk relationships. In addition, many of them did not include any quantification of radiation dose resulting from uranium exposure or did not use harmonized dosimetric approaches, which limits the comparability of their results (Canu et al 2008, Zhivin et al 2014.…”
Section: Introductionmentioning
confidence: 99%